2015
DOI: 10.1590/s1517-838246220140533
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization processes of calcite induced by bacteria isolated from marine sediments

Abstract: Biomineralization is a known natural phenomenon associated with a wide range of bacterial species. Bacterial-induced calcium carbonate precipitation by marine isolates was investigated in this study. Three genera of ureolytic bacteria, Sporosarcina sp., Bacillus sp. and Brevundimonas sp. were observed to precipitate calcium carbonate minerals. Of these species, Sporosarcina sp. dominated the cultured isolates. B. lentus CP28 generated higher urease activity and facilitated more efficient precipitation of calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(118 citation statements)
references
References 51 publications
4
97
0
6
Order By: Relevance
“…However, it also depends on the media; for example, solid or viscous media could enable the bacteria to capture Ca +2 more selectively and to precipitate calcite, while more liquid environments tend to precipitate aragonite (Rivadeneyra et al, 1998). Members of the Acinetobacter genus are known to produce aragonite, calcite or vaterite, depending on the media (Ferrer et al, 1988;Okyay and Rodrigues, 2015;Wei et al, 2015), but Acinetobacter gyllenbergii had not previously been reported to precipitate calcite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it also depends on the media; for example, solid or viscous media could enable the bacteria to capture Ca +2 more selectively and to precipitate calcite, while more liquid environments tend to precipitate aragonite (Rivadeneyra et al, 1998). Members of the Acinetobacter genus are known to produce aragonite, calcite or vaterite, depending on the media (Ferrer et al, 1988;Okyay and Rodrigues, 2015;Wei et al, 2015), but Acinetobacter gyllenbergii had not previously been reported to precipitate calcite.…”
Section: Discussionmentioning
confidence: 99%
“…precipitate calcium carbonate is still unknown (Hammes and Verstraete, 2002), the process is probably linked to the calcium carbonate precipitation conditions. These is usually induced by an increase in pH, high calcium concentration and the availability of nucleation sites, such as bacterial cell walls or other molecules (De Muynck et al, 2010;Wei et al, 2015) Even though mines are not strictly cave environments, since they have been constantly intervened by humans, culture-dependent and culture-independent analysis suggest that their biodiversity is quite similar to that of cave speleothems. Our analysis showed the presence of common genera that have been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Genera found within the Caulobacterales Order (Caulobacter and Brevundimonas) are ubiquitous in many different environments. They are oligotrophic and can metabolize aromatic hydrocarbons as well as plant-derived carbohydrates and organic acids [47,48].…”
Section: Othersmentioning
confidence: 99%
“…Calcite, vaterite and aragonite are three polymorphs of calcium carbonate precipitated by bacteria (Wei et al . ).…”
Section: Introductionmentioning
confidence: 97%